Professional Faculty Development Formation Through Course Refresher in Assessing and Facilitating Teaching Learning (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study aims to identify the process formation of professional faculty development through course refresher in assessing and facilitating teaching learning among the respondents as to skills productivity, school culture, update training trends, and development of teaching management. Hence, the mixed method is utilized in the research process through Focused Group Discussion (FGD) in the concrete analysis of the study. Likewise, purposive sampling is employed in the study which is convenience sampling drawn in accessible sources of the researcher in gathering the sample size of the population target process. The study comprised one hundred seventy five (175) respondents only.Results show to create things simple, focus plan, and faculty to stay on set tasks for success and clear outcome, skills productivity shows to improve focused of employee program and benefit toward performance goals of the school organization, school culture shows to build strong relationships which is one of the core values of Higher Education Institution to breed positive culture, update training trends shows to design the capability of faculty to improve approach in teaching trends based on the needs of students' learning process, and development of teaching management shows to define best possible teaching and development management to emphasize positive behavior for the learners-based needs teaching process.Findings show that there is a significant relationship on the process of professional faculty development through course refresher in assessing and facilitating teaching learning as observed among the respondents.